1999
DOI: 10.1097/00000478-199902000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Poorly Differentiated Thyroid Carcinoma

Abstract: The clinicopathological importance of a heterogeneous group of poorly differentiated thyroid carcinomas is not fully understood. Using data obtained from 303 surgically treated patients with differentiated thyroid carcinomas, the correlations between the aggressive histologic features and the clinicopathological findings, postoperative recurrences, and prognosis were retrospectively examined. In 201 cases, the carcinomas were well differentiated. The remaining 102 cases of poorly differentiated carcinomas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 20 publications
5
73
2
1
Order By: Relevance
“…Similarly, young age was associated with favorable prognosis, consistent with a number of other studies (16,18,21). Previous studies demonstrated that patients with HTC or FTC were more likely to show unfavorable clinical outcomes compared with those suffering from PTC (22)(23)(24). Consistently, the present study found that patients suffering from HTC or FTC upon diagnosis were more susceptible to bone metastases.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, young age was associated with favorable prognosis, consistent with a number of other studies (16,18,21). Previous studies demonstrated that patients with HTC or FTC were more likely to show unfavorable clinical outcomes compared with those suffering from PTC (22)(23)(24). Consistently, the present study found that patients suffering from HTC or FTC upon diagnosis were more susceptible to bone metastases.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, these carcinomas with insular pattern often show diffuse immunoreactivity for thyroglobulin, reflecting functional differentiation. Other investigators have emphasized cytologic features and include the tall-cell variant of papillary thyroid carcinoma in the poorly differentiated category, perhaps because of its aggressive clinical course (15,17). However, we believe that the height of the cell (tall cell) is not enough for this variant of papillary carcinoma to be considered poorly differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…Different terms have been used to refer to these tumors, including solid, 3 trabecular, 4 insular, 5,6 poorly differentiated, 3,7,8 …”
mentioning
confidence: 99%